Carbonized common filter paper decorated with Sn@C nanospheres as additive-free electrodes for sodium-ion batteries. (June 2015) - Chen, Wei; Deng, Da
Abstract: Sodium-ion batteries (SIBs) are, arguably, one of the most promising candidates for post-lithium ion battery era. The success of sodium-ion batteries is dependent on electrode materials developed. We reported here the facile preparation of carbonized filter paper decorated with Sn@C nanospheres as negative electrode materials for SIBs. The carbonized filter paper decorated with Sn@C nanospheres were obtained by in-situ carbonization of the cellulose paper fibers and the reduction of SnO2 to metallic Sn which were encapsulated with carbon sheaths by chemical vapor deposition (CVD). Particularly, both the carbon sheaths and the encapsulated Sn cores are spherical. The formation mechanism of the spherical Sn@C nanospheres was proposed based on unique properties of molten tin with high surface tension forming spherical droplets. The carbonized filter paper decorated with Sn@C nanospheres in the form of slices can be directly assembled into electrochemical cells without any further treatment or additives. Higher capacities and better Coulombic efficiencies than that of bare carbonized filter paper were achieved. The mechanism of capacity fading was investigated systematically by cyclic voltammetry (CV) and post-test analysis. This understanding will be helpful to design better Sn based electrodes for SIBs.